Effect of Stevia rebaudiana Bertoni extract on sexual dysfunction in Streptozotocin-induced diabetic male rats - Ghaheri, Matin; Miraghaee, Shahram; Babaei, Atefeh; Mohammadi, Bahareh; Kahrizi, Danial; Saivosh Haghighi, Zahra Minoosh; Bahrami, Gholamreza (Cellular and Molecular Biology, 2018)
Stevia rebaudiana Bertoni has been used locally as a non-calorie sweetener in medicine and diabetic diet which claimed to have aphrodisiac properties, although no scientific data of this function have been reported. The aim of this study was to investigate the effect of S. rebaudiana extract on sexual dysfunction, testosterone levels and number of Leydig cells in Streptozotocin (STZ)-induced diabetic male rats. A total of 28 diabetic male rats were randomly divided into 4 groups: diabetic group without any extract and 3 extract groups (5, 50 and 100 mg/kg). Seven normal control rats were treated with vehicle mount latency and frequency of (ML, MF), intromission latency and frequency (IL, IF), ejaculation latency and frequency of (EL, EF), the mount latency post ejaculation (MPE), the intromission latency post ejaculation (ILE), the intromission frequency post ejaculation (IFE) were recorded during 30 min on days 0, 14, 28. The serum testosterone levels, blood glucose, sex organs weight, number of leydig cells and histology of testicular tissue were measured. The stevia group (5 mg/kg) had a significant (p<0.05) increase in EF and IF. The number of Leydig cells in the diabetic group were significantly (p<0.05) reduced compared to the normal group and diabetic groups with extract (5 and 50 mg/kg). The serum testosterone levels and other sexual behaviors did not show any significant differences. The low- dose stevia extract with attention to antioxidant, vasodilator and anti-diabetic properties can be aphrodisiac in STZ- induced diabetic male rats.